Pengaruh Pemerintahan Taliban terhadap Pencapaian Tujuan SDGs 2030 bagi Perempuan di Afganistan - Siti Salsabila; Maulana Rifai (Faculty of Social and Political Sciences, Universitas Singaperbangsa Karawang, Indonesia, 2025)
The Taliban government that regained power in Afghanistan in 2021 has had a significant impact on women's lives, especially in terms of access to education, employment, and participation in political activities. This study aims to analyze the impact of discriminatory policies implemented by the Taliban on the achievement of the 2030 Sustainable Development Goals (SDGs), with a particular focus on gender equality (SDG 5). By adopting Amartya Sen's theoretical approach regarding the five instrumental freedoms, namely political freedom, economic opportunity, social opportunity, guarantees of transparency, and guarantees of security. This study reveals that restrictions on women's rights have exacerbated the feminization of poverty and restrictions on education and employment have deprived women of opportunities to improve their quality of life. Through qualitative research methods, this study collected data from various relevant literature sources, including scientific articles, news, and reports from international institutions that discuss the socio-economic conditions of women in Afghanistan. The findings of this study indicate that the policies implemented by the Taliban have hampered progress towards the 2030 SDGs by narrowing the space for women to participate in the public sector and the economy. Therefore, collective efforts from various global actors are crucial in ensuring that women in Afghanistan continue to have access to education, employment and their basic rights as part of a sustainable development agenda. Keywords: Afghanistan, SDGs, Feminization of Poverty, Five Instrumental Freedoms